Will Treatment of Helicobacter Pylori Infection in Childhood Alter the Risk of Developing Gastric Cancer? - Billy Bourke (Canadian Journal of Gastroenterology)
Helicobacter pylori has been classified as a group 1 carcinogen for gastric cancer. It is estimated that there is between a two- and sixfold increase in the risk of developing gastric cancer among infected patients. Among different populations, the risk of H pylori-infected individuals developing gastric cancer varies greatly. However, on a worldwide scale, gastric cancer is the second most common cause of cancer-related death. Therefore, H pylori eradication could help prevent up to three to four million gastric cancer deaths per year. H pylori is usually acquired in childhood. Because infected children have not harboured the organism for long enough to have developed precancerous lesions, childhood is theoretically an attractive time for H pylori eradication and, thus, could help prevent gastric cancer later in life. However, as H pylori prevalence and the incidence of gastric cancer are falling rapidly in developed nations, widespread population screening programs aimed at the eradication of H pylori in these countries would be enormously expensive. Therefore, except in groups with a high risk for development of gastric cancer (eg, Japanese or those with a strong positive family history of gastric cancer), a population-based test-and-treat policy is not justified.